An error-bounded B-spline curve approximation scheme using dominant points for CNC interpolation of micro-line toolpath. (August 2020) - Du, Xu; Huang, Jie; Zhu, Li-Min; Ding, Han
Highlights: The bi-chord error test fully considers the geometric properties of the micro-line toolpath. The bi-chord errors test greatly reduces the impact of noisy points on the number and distribution of the dominant points. The chord error estimation for the B-spline curve approximation analytically determines whether or not the geometric deviation between the polygon formed by the micro-line toolpath and the initial B-spline curve is under the chord error constraint. Abstract: This paper presents a unified framework for computing a B-spline curve to approximate the micro-line toolpath within the desired fitting accuracy. First, a bi-chord error test extended from our previous work is proposed to select the dominant points that govern the overall shape of the micro-line toolpath. It fully considers the geometric characteristics of the micro-line toolpath, i.e., the curvature, the curvature variation and the torsion, appropriately determining the distribution of the dominant points. Second, an initial B-spline curve is constructed by the dominant points in the least square sense. The fitting error is unpredictable and uncontrollable. It is classified into two types: (a) the geometric deviations between the vertices of the polygon formed by the data points and the constructed B-spline curve; (b) those between the edges of the polygon and the constructed B-spline curve. Herein, an applicable dominant point insertion is employed to keep the first geometric deviation within the specified tolerance of fitting error. A geometric deviation model extended from our previous work is developed to estimate the second geometric deviation. It can be effectively integrated into global toolpath optimization. Computational results demonstrate that the bi-chord error test applies to both the planar micro-line toolpath and the spatial micro-line toolpath, and it can greatly reduce the number of the control points. Simulation and experimental results demonstrate that the proposed B-spline approximation approach can significantly improve machining efficiency while ensuring the surface quality.